A New Technique for Direct Fabrication of Fiber-Reinforced Composite Bridge: A Long-Term Clinical Observation - Matías Ferrán Escobedo Martínez; Samuel Rodríguez López; Jairo Valdés Fontela; Sonsoles Olay García; Mario Mauvezín Quevedo (Dentistry Journal, 2020)
The use of fiberglass in dentistry has increased due to the improvements in the development of adhesive techniques reducing the cost of treatment and avoiding abutment tooth craving. The present study aims to evaluate the clinical usefulness of the new technique to fabricate a direct fiber-reinforced composite bridge (FRCB) over a long period of time. Twenty-one FRCB were performed with the new direct technique on 21 patients with a mean age of 58.85 years and female predominance in the Faculty of Dentistry of Oviedo (Spain). The framework design releases the embrasures allowing adequate interproximal brushing, avoidance of periodontal disease and interproximal caries. A baseline examination was performed and the patients were examined regularly at six-month intervals (nine years’ follow-up). The restorations were also evaluated by an examiner using parameters to check their stability, longevity and the lack of periodontal disease. The most frequent location was the maxillary premolar region and the purpose of the restorations was to give a definitive bridge in 100% of the patients. Only one total debonding of the prostheses was detected during the observation period at 24 months and three partial adhesive–cohesive veneering composite fractures at the pontic after 60, 72 and 84 months, respectively. Kaplan–Meier was performed to detect the overall survival rate of the restorations at the end of the follow-up. Nine-year survival rates for the FRCB was 95.2%. All the cases had a clinically acceptable periodontal condition and an interproximal absence of caries in the abutment teeth. Currently, this type of restoration allows a minimally invasive aesthetic and is an affordable procedure, being a good alternative to other types of treatments.